Becoming a manager : - Hill, Linda A. (Harvard Business School Press, 2019)
In your career, or anyone's, there is one transition that stands out as the most crucial--going from individual performer to competent manager. New managers have to learn how to lead others rather than do the work themselves, to win trust and respect, to motivate, and to strike the right balance between delegation and control. Many fail to make the transition successfully. In this timeless, essential book, Harvard Business School professor and leadership guru Linda Hill traces the experiences of nineteen new managers over the course of their first year in the role. She reveals the complexity of the transition, highlighting the expectations of the managers, their subordinates, and their superiors. We hear the new managers describe how they reframed their understanding of their roles and responsibilities, how they learned to build effective work relationships, how and when they used individual and organizational resources, and how they learned to cope with the inevitable stresses of leadership. Hill shows that becoming a manager is a profound psychological adjustment--a true transformation--as well as a process of learning from experience. And she also offers concrete advice on dealing effectively with organizational politics, developing and leading diverse teams, and how managers can prepare themselves to lead over the course of their careers.